1993
DOI: 10.1111/j.1502-3885.1993.tb00185.x
|View full text |Cite
|
Sign up to set email alerts
|

The vertical extent of ice sheets in Nordfjord, western Norway: measuring degree of rock surface weathering

Abstract: Degree of rock surface weathering was measured on sites in Oldedalen and Brigsdalen, where dates of deglaciation have been estimated. and on an altitudinal transect on the slopes of Skåla. representing one of the highest supra‐marine reliefs in western Norway. The Schmidt hammer is useful only for distinguishing sites deglaciated during the Little Ice Age from those deglaciated during the Lateglacial and early Holocene. Degree of roughness of granitic augen gneiss bedrock surfaces was quantified from profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…; another trimline is evident at 1350 m a.s.l., and the lowest trimline, which has been interpreted as the Younger Dryas ice limit, is positioned at c. 1100 m a.s.l. (Nesje et al 1988;McCarroll & Nesje 1993). While a thin, cold-based ice sheet covering mountain peaks in the area and protecting the highest elevations from erosion cannot be ruled out by cosmogenic results alone (Brook et al 1996), comparison with our model results indicates that the highest trimline most likely represents the maximum ice thickness during the last glaciation.…”
Section: Ice Thicknessmentioning
confidence: 79%
See 1 more Smart Citation
“…; another trimline is evident at 1350 m a.s.l., and the lowest trimline, which has been interpreted as the Younger Dryas ice limit, is positioned at c. 1100 m a.s.l. (Nesje et al 1988;McCarroll & Nesje 1993). While a thin, cold-based ice sheet covering mountain peaks in the area and protecting the highest elevations from erosion cannot be ruled out by cosmogenic results alone (Brook et al 1996), comparison with our model results indicates that the highest trimline most likely represents the maximum ice thickness during the last glaciation.…”
Section: Ice Thicknessmentioning
confidence: 79%
“…However, new preconsolidation tests on samples from the same site (Skorgedalen, western Norway, at c. 63 N), using the constant strain rate method rather than incremental loading, indicate substantially lower minimum ice thickness close to the elevation of the trimline (Hildreth 2001). Based on roughness measurements at Skåla, in the Nordfjord area, which indicate the degree of rock surface weathering, McCarroll & Nesje (1993) concluded that the ice during the LGM either extended over all summits, but was cold-based and therefore did not erode the bedrock, or its maximum vertical limit was even lower than previously suggested (at c. 1350 m a.s.l. ).…”
mentioning
confidence: 78%
“…on Finnan (cf. Nesje and Dahl, 1990;McCarroll and Nesje, 1993;Nesje et al, 1994;Brook et al, 1996;Goehring et al, 2008). Despite its westerly location, permafrost is likely to have extended into the bedrock at altitudes above and beneath relatively thin coldbased ice at this site at this time (cf.…”
Section: The Legacy Of Glaciers and Glacier-permafrost Interactionmentioning
confidence: 92%
“…Rock surface roughness can be used to compare the effects of weathering where it is assumed that initial surface texture was roughly the same (McCarroll and Nesje, 1993Nesje, , 1996. This can then be used as an indicator of the relative time that a rock surface has been exposed to weathering processes.…”
Section: Profile Gaugementioning
confidence: 99%
“…Rebound values (R-values) produced by the impact of the hammer decline with increased rock-surface weathering, and so can be used as a relative measure of exposure history (McCarroll, 1991;McCarroll and Nesje, 1993;Nesje et al, 1994;Goudie, 2006;Shakesby et al, 2011). We used an N-type Schmidt hammer to analyse 50 boulders from two of the boulder trains thought to be from different glacial cycles (BI 1 and RC 1).…”
Section: Schmidt Hammermentioning
confidence: 99%